Postsurgical Treatment in Pediatric Patients With Crohn's Disease: Physician Practice. Issue 5 (15th December 2020) - Magen-Rimon, Ramit; Garah, Jamal; Rosen, Irit; Shaoul, Ron
Abstract : The aim of this study was to evaluate the implementation of the pediatric Crohn's disease postsurgical guidelines using an online questionnaire among North American, European, Middle Eastern, Australian, and New Zealand pediatric gastroenterologists. We found high variability in practice and low adherence to guidelines.